VD_FINDINFO HC / 2010 / 154 vom 19. Januar 2010 - VD Tribunal cantonal (2010)
MODÉRATION, HONORAIRES, AVOCAT, DÉCOMPTESENS GÉNÉRAL, FARDEAU DE LA PREUVE, OBLIGATION DE RENSEIGNER | 8 CC, 12 let. i LLCA, 45 al. 1 LPAv, 48 LPAv, 51 LPAv